Cytotoxicity, antioxidant activity and chemical constituents of piper sarmentosum ethanolic extract - Ibrahim, Maizatul Akma; Mohd Nasir, Mohd Hamzah; Azahari, Nur Fathihah Suraya (IIUM, 2020)
Plants hold a high value for mankind due to its richness in properties. Plants secondary metabolites are of particular interest as they possess medicinal properties that can be utilised by human. Among local plants of interest is Piper sarmentosum that is locally known as Kaduk. It is a plant from Piper species with numerous medicinal properties. This study evaluated the cytotoxicity property, antioxidant activity, and chemical composition for P. sarmentosum of ethanolic extract. The leaves of P. sarmentosum were extracted through Soxhlet method using absolute ethanol. The cytotoxic study was performed through MTT ((3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay using HT-29 human colon adenocarcinoma cell line, while antioxidant activity assessed through 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay. The crude was also evaluated for its chemical constituents by gas chromatography coupled with mass spectrometer (GC-MS). Results demonstrated that the cytotoxicity effect of P. sarmentosum on HT-29 was exhibited with an IC50 of 25 Âµg/mL. The same extract was also found to exhibit antioxidant activity by DPPH scavenging assay with an IC50 of 126.39 Âµg/mL. These findings suggested that the ethanolic extract of P. sarmentosum was relatively active and may be considered as potent agents for future healthcare and pharmaceutical industries.